OBESITY AND DYSLIPIDEMIA IN CHILDREN WITH CHRONIC HEPATITIS - Alice N. Azoicai; Bogdan A. Stana; Paula Popovici; Ileana K. Ioniuc; Monica M. Alexoae; Irina Criscov; Alina M. Murgu; Evelina Moraru (Amaltea Medical Publishing House, 2016)
Chronic hepatitis association with various types of dyslipidemia is a reality not only for the obese pediatric patient, in which we expect to find hypercholesterolemia and / or hypertriglyceridemias, but also for normal weight children with hepatitis. The causes of this association are multiple, but we need to consider first the innate predisposition and transmission of genetic forms of dyslipidemia. Meanwhile, some secondary dyslipidemia are chronic liver disease related. Those considerations are forming a vicious circle in which primary treatment of metabolic imbalances has a great importance for the success of antiviral therapy.